Prognostic outcome of local recurrence in breast cancer after conserving surgery and mastectomy - Soumarová, Renata (Radiology and oncology (Ljubljana), 2003)
Background. In our retrospective study we analysed local recurrences in breastcancer patients treated with conserving surgery (CS) followed by adjuvant radiotherapy (RT) or mastectomy (ME) with or without radiotherapy. Weanalysed the impact of local recurrence on overall survival. Patients and methods. Between 1980-1995, 306 patients underwent conserving surgery and 1,193 patients were done mastectomy in Masaryk Memorial Cancer Institute. The patients lost to follow-up were excluded. After all, we analysed 236 patients who underwent conserving surgery (Group A), and 1,121 who underwent mastectomy(Group B). All patients with CS received adjuvant RT of the breast with or without regional lymph nodes. In 982 patients (87,6%) with ME, we performed RT of the chest wall or without regional lymph nodes. Median age at the time of diagnosis was 48.3 years in Group A and 52.1 years in Group B. In Group A, 149 patients (63.1%) had T1 tumour, 86 (36.4%) T2 and 1(0.5%)T3. In 24.2% of patients, axillary node involvement was observed. In Group B, 316 patients (30.4%) had T1 tumour. 607 (58.3%) T2, 76 (7.3%) T3, 33 (3.2%) T4 and9 (0.9%) TX. In 46.2% of these patients, we found axillary node involvement. Invasive ductal carcinoma was histologically proved in 67.4% in Group A and 84% in Group B. Systemic treatment was given to 133 patients (56.4%) from Group A and to 857 patients (76.4%) from Group B. Results. Medianfollow-up was 100.5 months in Group A and 121 months in Group B. In Group A, we registered 22 (9.3%) local recurrences, 5-year local control was 96.2% and median time to local recurrence was 50 months. In Group B, we registered 65 (5.8%) local recurrences; 5-year local control was 96.6%. Five-year local control in patients with T1, T2 tumours was 97.2%. In patientswith adjuvant RT median time to local recurrence was 48.5 months, and in patients without adjuvant RT 51 months. (Abstract truncated at 2000 characters).
Keywords: breast; Breast Neoplasms; Dojka, novotvorbe; dojke; kirurško zdravljenje; Mastectomy; Mastektomija; Neoplasm Recurrence, Local; Neoplasm Staging; Novotvorba, ponovitev lokalna; Novotvorba, stadij; Preživetje, analiza; Prognosis; Prognoza; Radioterapija pomožna; Radiotherapy; Radiotherapy, Adjuvant; rak (medicina); Retrospective Studies; Retrospektivne študije; Surgery; Survival Analysis; therapy; zdravljenje